Controlling molecular weight cut-off of PEEK nanofiltration membranes using a drying method - Da,Silva Burgal J; Peeva,L; Marchetti,P; Livingston,A (Journal of Membrane Science, 2015)
In this research paper we report two ways of controlling the molecular weight cut-off (MWCO) of PEEK membranes prepared via phase inversion and subsequent drying. The two methods explored were the change of polymer concentration in the dope solution – 8 wt. %, 10 wt. % and 12 wt. %-and the variation of solvent filling the pores prior to drying – e.g. water, methanol, acetone, tetrahydrofuran and n-heptane. The results show that it is possible to vary the MWCO from 295 g.mol−1 to 1400 g.mol−1 by varying these parameters. A statistical analysis based on a genetic algorithm showed that the Hansen solubility parameter, polarity and their interactions with molar volume were likely to be the most important parameters influencing the performance of PEEK membranes when drying from different solvents. In addition, the drying temperature also proved to have an effect on the membrane performance-the higher the temperature the higher the rejection and the lower the permeance.